2015
DOI: 10.3233/npm-15814071
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuing caffeine in preterm infants at 33–35 weeks corrected gestational age: Failure rate and predictive factors

Abstract: Caffeine can be discontinued at 33-35 weeks PMA with a failure rate of 10%. BPD and Hispanic ethnicity are predictive of failure. It is generally safe to discharge infants seven days after the caffeine was discontinued if no significant monitor events occur during that time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…For example, caffeine therapy, given for apnoea of prematurity, is stopped in infants between 33-35 weeks PMA if the infant appears clinically stable 25 . However, in 10% of infants caffeine treatment is restarted 26 , which may suggest that caffeine was withdrawn too early, exposing the infants to the adverse consequences of lack of treatment. We found that 88% of apnoeas identified using our algorithm were missed in the clinical notes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, caffeine therapy, given for apnoea of prematurity, is stopped in infants between 33-35 weeks PMA if the infant appears clinically stable 25 . However, in 10% of infants caffeine treatment is restarted 26 , which may suggest that caffeine was withdrawn too early, exposing the infants to the adverse consequences of lack of treatment. We found that 88% of apnoeas identified using our algorithm were missed in the clinical notes.…”
Section: Discussionmentioning
confidence: 99%
“…While the benefits of caffeine therapy are well studied, the appropriate timing of discontinuation relative to infant discharge from the hospital is unknown. Neonatologists typically observe infants for the completion of an "event-free" period after the discontinuation of caffeine therapy as a prerequisite for discharge; [11] however, no consensus among clinicians currently exists in regards to what length of apnea-free period is adequate enough to determine safe discharge [12]. Notably, some infants are discharged home on caffeine as a means of achieving earlier hospital discharge [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, caffeine therapy, given for apnoea of prematurity, is stopped in infants between 33 and 35 weeks PMA if the infant appears clinically stable. 26 However, in 10% of infants, caffeine treatment is restarted, 27 which may suggest that caffeine was withdrawn too early, exposing the infants to the adverse consequences of lack of treatment. We found that 88% of apnoeas identified using our algorithm were not recorded in the medical records, consistent with previous results highlighting the inaccuracies in clinical documentation of apnoea.…”
Section: Discussionmentioning
confidence: 99%